BURNOUT SYNDROME AMONG NURSES DURING COVID-19 PANDEMIC - Sri Hananto Ponco Nugroho; Puguh Widiyanto (Universitas Muhammadiyah Yogyakarta, 2022)
COVID-19 pandemic has threatened public health all over the world. All healthcare professionals especially nurses are at risk of experiencing health problems either physically or psychologically. One of which is burnout syndrome. This research aimed to identify burnout syndrome among nurses. The research applied a descriptive analytics design with a cross-sectional approach. The samples were 134 nurses in a hospital in Magelang regency who obtained from purposive sampling. The data were gathered through Maslach Burnout Inventory (MBI). Then, the data were analyzed through mean value distribution. The results showed that nurses' burnout syndrome was in a low category. Furthermore, the nurses' emotional exhaustion was in the moderate category, depersonalization was in a low category, and reduced personal accomplishment was in a low category.